The attitudes and perceptions of beginning teachers in relation to teaching controversial and sensitive issues in the history classroom - Woolley, Mary Catherine (Revista Electrónica Interuniversitaria de Formación del Profesorado, 2017)
This paper reports on research into the attitudes and perceptions of beginning history teachers in relation to teaching controversial and sensitive issues. In 2007 the UK Department of Education and Skills, alongside the Historical Association, published a report into the teaching of emotive and controversial issues in history which suggested avoidance of some topics by some teachers. Initial research was carried out with 32 beginning history teachers to explore their attitudes to teaching controversial issues in the history classroom. Ten years later, the research was repeated with a further cohort to explore whether attitudes had changed. Findings showed an enthusiastic, almost moralistic group of beginning teachers, committed to sharing a wide range of views with their young audience. The beginning teachers were remarkably confident about teaching controversial and sensitive issues. The area where beginning teachers lacked confidence was in dealing with parents who disagreed with their approach to teaching a certain topic. Almost all the beginning teachers thought it was appropriate for history teachers to teach topics in a way that might conflict with family or cultural values. New concerns have emerged for some beginning teachers over how to teach the history of migration in a sensitive and appropriate way.